2010
DOI: 10.1007/s10482-010-9490-9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of culturable thermo-resistant aquatic bacteria along an environmental gradient in Cuatro Ciénegas, Coahuila, México

Abstract: At the desert oasis of Cuatro Ciénegas in Coahuila, México, more than 300 oligotrophic pools can be found and a large number of endemic species of plants and animals. The most divergent taxa of diatoms, snail and fishes are located in the Churince hydrological system, where we analyzed the local diversification of cultivable Firmicutes and Actinobacteria. The Churince hydrological system is surrounded by gypsum dunes and has a strong gradient for salinity, temperature, pH and dissolved oxygen. In August 2003, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 49 publications
(51 reference statements)
5
70
0
Order By: Relevance
“…Schuman et al [30] suggested that Cellulomonas should be reclassified as Cellulosimicrobium. Cellulomonas has previously been reported as a culturable thermoresistant aquatic bacterium from the oligotrophic pools in Mexico [27]. To our knowledge, this is the first report on Aurantimonas and Brevundimonas in a hot spring.…”
Section: Citationmentioning
confidence: 60%
See 2 more Smart Citations
“…Schuman et al [30] suggested that Cellulomonas should be reclassified as Cellulosimicrobium. Cellulomonas has previously been reported as a culturable thermoresistant aquatic bacterium from the oligotrophic pools in Mexico [27]. To our knowledge, this is the first report on Aurantimonas and Brevundimonas in a hot spring.…”
Section: Citationmentioning
confidence: 60%
“…Among the different genera obtained from Vashist hot springs Exiguobacterium, Kocuria and Brevibacillus were reported in our earlier study on diversity of thermotolerant bacteria from Manikaran [21] and also in the studies on the diversity of culturable thermoresistant aquatic bacteria in Mexico [27]. Representatives from Acinetobacter, Enterobacter and Gulbenkiania, which are pathogens and associated with human intestine, may have been transmitted as contaminants from people taking shower in the spring, as this spring is known for its medicinal properties.…”
Section: Citationmentioning
confidence: 86%
See 1 more Smart Citation
“…This has led to the hypothesis that bacteria in the CCB water systems are descendants of marine bacteria from Pre-Cambrian (Souza et al 2006). Systematic studies have also been used to describe new species of bacteria using current criteria (Anderson et al 2005;Cerritos et al 2008;Ehling-Schulz et al 2005;Escalante et al 2009;Helgason et al 2004) as well as by attempting to apply multivariate analysis and physical-chemical analyses in order to determine special relationships amongst the bacteria (Cerritos et al 2011). At the genomic scale, 2 genomes (Alcaraz et al 2010;Alcaraz et al 2008) and 3 metagenomes (Breitbart et al 2009;Desnues et al 2008;Dinsdale et al 2008) had been described, in which genes that allow for adaptation to the oligotrophic environment of Cuatro Cienegas have been identified.…”
Section: Bacterial Genomics Of Two Bacterial Isolates From the Ccb Prmentioning
confidence: 99%
“…Thus, the high diversity of CCB would be a product of two things: the diversity already present at the time of isolation, and the new community assemblages that arose in this unique aquatic environment Souza et al 2006). Firmicutes, an abundant and widespread genera within CCB (Alcaraz et al 2010;Alcaraz et al 2008;Cerritos et al 2011;Moreno-Letelier et al 2011;Souza et al 2006) are the focal group of our studies, in part because there are several endemic species within the site, and because the whole genome has been sequenced for both Exiguobacterium and Bacillus isolates (Bacillus coahuilensis m4-4 ; Bacillus sp. m3-13 (Alcaraz et al 2010); and several unpublished data (from drafts Bacillus sp.…”
Section: Molecular Clockmentioning
confidence: 99%